Simultaneous determination of paracetamol, 4-Aminophenol, 4-Chloroacetanilid, Benzyl alcohol,Benzaldehyde and EDTA by HPLC methodin paracetamol injection ampoule - Ali Merrikhi Khosroshahi; Fereydoon Aflaki; Nader Saemiyan; Assem Abdollahpour; Ramin Asgharian (Islamic Azad University, 2016)
Paracetamol that is known as acetaminophen have the most consume as an analgesic and antipyretic drug in the world. That is formulated in single compound or mixture at many forms such as tablets, syrups, suspensions and drops. The last form is intravenous injections. Paracetamol derived from 4-minophenol which is synthesized by acylated the P-acetaminophenol and acetic anhydride. 4-aminophenol is the main impurity at manufacturing of paracetamol which could produce by hydrolysis during storage or synthesis under normal conditions (temperature, pH, etc.). Also, 4-chloroacetanilid may be observed as an impurity in the raw material of paracetamol synthesis. Benzyl alcohol is a preservative that used in Paracetamol for injection. It will be very important if there are analytical techniques to measuring paracetamol and its degradation products accurately and easily. Undoubtedly the most important and widely used, separation technique is chromatography. There are several reports about separation and quantitative determination of paracetamol lonely or simultaneous determination of paracetamol and 4-aminophenol. In this paper investigated simultaneous determination of paracetamol, 4-aminophenol, 4-chloroacetanilid, benzyl alcohol, benzaldehyde, and EDTA in paracetamol for injection ampoules by high performance liquid chromatography. By changing the ratio of mixing methanol and acetonitrile as mobile phase at the wavelength of 215 nm and pH=3 separation of all compounds were completely done.